HUBUNGAN SIKAP BERLATIH DENGAN MOTIVASI BERLATIH ATLET PPLP SEPKABOLA PPLP DISPORA PROVINSI RIAU TAHUN 2019 - Afrizul Mz; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this study was to determine the relationship between the attitude of the practice and the motivation to practice on PPLP football athletes DISPORA Riau Province in 2019. The type of research used was associative (correlational). Sukmadinata (2005: 56) explains that correlational research is intended to determine the relationship of a variable with other variables, the relationship between one with different other variables expressed by the magnitude of the correlation coefficient and significance (significance) statistically. The population in this study was PPLP DISPORA football athlete in the Riau province. The data analysis technique used in this study uses quantitative descriptive analysis techniques with percentages (Anas Sudijono, 2012: 40). The obtained numbers are summed and the results are compared with the expected number of scores to obtain a percentage. Moreover, the percentage is interpreted in quantitative sentences. The results of the study are practical certificates, test data for the average value is 67.44, the highest value = 76, the lowest value = 62, median = 68.50, variance = 17.59, standard deviation = 4.19. And the training motivation test data for the average value is 65.94, the highest score = 74, the lowest value = 55, median = 65.50, variance = 25.8, standard deviation = 5.08. After the data is obtained, it is descriptively analyzed, and the next one is to test the proposed research hypothesis in accordance with the proposed problem. The hypothesis that reads: There is a significant relationship between the attitude of training (X) and motivation (Y) in Dispora football athletes in the province of Riau. Based on the obtained correlation coefficient of r count = 0.9356> of rtable = 0.514, so Ha is accepted. This means that there is a connection between the attitudes of practice and the motivation to practice, whereby the determination of a variable correlation with other variables is determined on the basis of r-number> r (Sugiyono, 2008: 258).Key Words: Practice with attitudes, motivation to practice, football.